Dissimilar tungsten inert gas welding between Inconel 718 and commercially pure titanium using a vanadium interlayer. (April 2022) - Shehbaz, Tauheed; Junaid, Massab; Khan, Fahd Nawaz; Akbar, Usman Ali; Saeed Hakeem, Abbas
A weight reduction of aero engines, in order to enhance their efficiency would be possible if the commercially pure titanium in the low-temperature region of the compressor could be welded with Inconel in the high-temperature portion. This joining of titanium/Inconel is challenging owing to the formation of hard Tix Niy intermetallic compounds, the suppression of which is not possible using the conventional weld process optimization approach. In recent years, a number of approaches have been developed to reduce or eliminate these intermetallic compounds during welding and one approach is the use of an interlayer during the welding operation. The insertion of a V interlayer at the root side remarkably suppressed Ti and Ni diffusion across the interlayer. NiV3 and (Ti, V) solid solutions were present in the interfacial microstructure of V/Inconel 718 and V/commercially pure titanium, respectively, as characterized by scanning electron microscope and X-ray diffraction. The tensile strength of the weldment was 190 MPa (approx. 59% of the commercially pure titanium base metal) with an elastic modulus comparable with that of the base alloys. The joint exhibited brittle fracture at the Inconel 718 side near the V/Inconel 718 interface due to intermetallic compounds.